2005
DOI: 10.1007/s11136-004-5328-0
|View full text |Cite
|
Sign up to set email alerts
|

Is treatment adherence associated with better quality of life in children with sickle cell disease?

Abstract: The association of treatment adherence with quality of life (QOL) and the role of sickle cell disease complications were explored in children with sickle cell disease. Primary caregivers of 43 children, ages 5 years and older, and 21 children, ages 8 years and older, completed a standardized measure of QOL during an admission for pain or fever to the hematology acute care unit. Adherence was measured through medical staff ratings, caregiver-report of sickle cell disease-related care activities, and matching of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 18 publications
1
19
1
1
Order By: Relevance
“…Furthermore, quality of life may differ for patients with the same ''objective'' health status and health status is not consistently associated with perceived interference with functioning, making this an essential end point to consider. 41,42 A combination of methodologies, both self-report, other report, and medical file review, would present the most complete assessment of adolescent health at any given point in time.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, quality of life may differ for patients with the same ''objective'' health status and health status is not consistently associated with perceived interference with functioning, making this an essential end point to consider. 41,42 A combination of methodologies, both self-report, other report, and medical file review, would present the most complete assessment of adolescent health at any given point in time.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that daily oral HU use is associated with reduced pain crises, hospitalizations, acute chest syndrome, and transfusions and improved growth and health-related quality of life [59]. Thus, the consequences of nonadherence to clinic attendance and HU treatments result in increased morbidity [10], healthcare costs [11], and decreased quality of life [12]. …”
Section: Introductionmentioning
confidence: 99%
“…There is very little information on the HRQL of children with SCD either during or following a vaso-occlusive painful event. One prior study measured HRQL upon admission for a painful event; however, the purpose of their study was to measure the association between adherence and HRQL [13]. In addition, there is no research evaluating the ability of HRQL measures to detect change over time in children with SCD.…”
Section: Introductionmentioning
confidence: 99%